Obtaining and evaluation of enzymatic extract from Aspergillus spp. by saccharification of sour cassava starch liqued - Andrés M. Rueda; Luis J. Rueda; Daniel Molina V.; Clara I. Sánchez (Revista Ion)
The saccharification enzymes are more expensive than liquefaction enzymes for that reason are sought strategies that allow the supply of these enzymes at low cost. The objectives of this study were to evolve saccharolytic enzymatic extracts from native strains, to select an extract and to determine the best variables for the production of glucose syrups from liquefied bitter cassava starch.Thirteen mushrooms isolated from sour cassava (Manihot sp). were evaluated for their saccharolytic activity, hydrolysis of maltose, glucose production and biomass formation in submerged fermentation. Aspergillus A1 was selected because it had the highest volumetric activity (0.09UI.L-1). During solid-state fermentation, the presence of proteins was corroborated by electrophoresis SDS-PAGE. Through various experiments, the best experimental condition were pH 4.0, agitation 0r.p.m and temperature 55.0°C; the effect of cofactors Cu2+, K+, Mg2+ and Na+ was evaluated, Mg2+ increases the activity in 1.32UImg-1 (32.4%). The thermal stability at 55.0°C is 120 minutes. Finally, the saccharolytic capacity of the enzymatic extract was confirmed using liquefied cassava starch.